SLPI Inhibits ATP-Mediated Maturation of IL-1β in Human Monocytic Leukocytes: A Novel Function of an Old Player - Zakrzewicz, Anna; Richter, Katrin; Zakrzewicz, Dariusz; Siebers, Kathrin; Damm, Jelena; Agné, Alisa; Hecker, Andreas; McIntosh, J. Michael; Chamulitrat, Walee; Krasteva-Christ, Gabriela; Manzini, Ivan; Tikkanen, Ritva; et al. (Frontiers in Immunology, 2019)
Interleukin-1β (IL-1β) is a potent, pro-inflammatory cytokine of the innate immune system that plays an essential role in host defence against infection. However, elevated circulating levels of IL-1β can cause life-threatening systemic inflammation. Hence, mechanisms controlling IL-1β maturation and release are of outstanding clinical interest. Secretory leukocyte protease inhibitor (SLPI), in addition to its well-described anti-protease function, controls the expression of several pro-inflammatory cytokines on the transcriptional level. In the present study, we tested the potential involvement of SLPI in the control of ATP-induced, inflammasome-dependent IL-1β maturation and release. We demonstrated that SLPI dose-dependently inhibits the ATP-mediated inflammasome activation and IL-1β release in human monocytic cells, without affecting the induction of pro-IL-1β mRNA by LPS. In contrast, the ATP-independent IL-1β release induced by the pore forming bacterial toxin, nigericin is not impaired, and SLPI does not directly modulate the ion channel function of the human P2X7 receptor heterologously expressed in Xenopus laevis oocytes. Using specific inhibitors and siRNA, we demonstrate that SLPI activates the calcium-independent phospholipase A2β (iPLA2β) and leads to the release of a low molecular mass factor that mediates the inhibition of IL-1β release. Signaling involves nicotinic acetylcholine receptor subunits α7, α9, α10, and Src kinase activation and results in an inhibition of ATP-induced caspase-1 activation. In conclusion, we propose a novel anti-inflammatory mechanism induced by SLPI, which inhibits the ATP-dependent maturation and secretion of IL-1β. This novel signaling pathway might lead to development of therapies that are urgently needed for the prevention and treatment of systemic inflammation.